Hunger and the global agenda : who wins, who loses, who cares? - KRONICK, Charlie (1996)
Points out that the problem of food insecurity - official language for not having enough to eat - is not just one of global food supplies, but of access to that food. Recognises that food security is more a political and structural problem than a technical one of food production. Notes the belief of most governments that market liberalization will benefit everyone 'eventually', and argues that the benefits of trade are not always equally distributed.